B lymphocytes directly contribute to tissue fibrosis in IgG4-Related Disease - Della-Torre, Emanuel (J Allergy Clin Immunol, 2019)
BACKGROUND: IgG4-related disease (IgG4-RD) is a fibro-inflammatory condition marked by rapid clinical improvement after selective depletion of B lymphocytes with rituximab. This feature suggests that B cells might participate in fibrogenesis and wound healing. OBJECTIVE: In the present work we aimed to demonstrate that B lymphocytes contribute directly to tissue fibrosis in IgG4-RD. METHODS: Total circulating CD19(+) B-lymphocytes, naïve B cells, memory B cells, or plasmablasts from IgG4-RD patients were cultivated with human fibroblasts. Pro-fibrotic soluble factors and collagen production in the co-cultures were assessed by ELISA and Luminex assays. RNA-sequencing and quantitative RT-PCR were used to assess fibroblast activation in the presence of B cells, as well as the induction of pro-fibrotic pathways in B cell subsets. Relevant pro-fibrotic and inflammatory molecules were confirmed in vitro by functional experiments and on IgG4-RD tissue sections by multi-color immunofluorescence studies. RESULTS: B cells from IgG4-RD patients (i) produced the pro-fibrotic molecule PDGF-B and stimulated collagen production by fibroblasts; (ii) expressed enzymes implicated in extracellular matrix remodeling such as LOXL2; (iii) produced the chemotactic factors CCL-4, CCL-5, and CCL-11; and (iv) induced the production of these same chemokines by activated fibroblasts. Plasmablasts expressed sets of genes implicated in fibroblast activation and proliferation, and therefore represent cells with intrinsic pro-fibrotic properties CONCLUSION: We have demonstrated that B cells, contribute directly to tissue fibrosis in IgG4-RD. These unanticipated pro-fibrotic properties of B lymphocytes, particularly of plasmablasts, might be relevant for fibrogenesis in other fibro-inflammatory disorders and for wound healing processes in physiological conditions.